Analysis of Criminalization of Perpetrators of Human Trafficking Crimes Based on the Trilogy of Legal Objectives - Dioz Thimoteus Togatorop; Maya Shafira; Muhammad Farid; Heni Siswanto; Refi Meidiantama (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the modus operandi of human trafficking in Indonesia, its legal framework, and the application of criminal sanctions to perpetrators based on the legal objectives of justice, certainty, and utility. Methodology/approach: Using secondary sources and a normative juridical approach, this study analyzes statutes, regulations, and legal concepts through a descriptive-analytical method to assess the consistency of legislation and its application in human trafficking cases. Results/findings: Findings show that human trafficking in Indonesia involves sexual exploitation, forced labor, child trafficking, and organ trade, regulated under Law No. 21/2007, the Criminal Code, and Law No. 35/2014 on Child Protection. Conclusions: Human trafficking in Indonesia includes sexual exploitation, forced labor, child trafficking, and organ trade. It is addressed through Law No. 21/2007 as a lex specialis, supported by the Criminal Code and Child Protection Law. Limitations: This study uses a normative juridical analysis at a macro level, without empirical field data or direct perspectives, so it does not fully capture local implementation issues or judicial inconsistencies. Contribution: This research offers a theoretical and practical framework for harmonizing the trilogy of legal objectives in criminalizing human trafficking and sentencing policies in Indonesia.